Fire on the horizon - Smith, Wilbur A.; Robertson, Imogen, 1973- (Courtneys & Ballantynes, 2024)
A familiar foe. A battle for the heart of a country at war with itself. South Africa, 1899 - the smouldering hostility between the Boers of the Transvaal and Orange Free State and the British colonies of the Cape and Natal is about to burst into flame. War is coming and no one can prevent it. Colonel Penrod Ballantyne, hero of Abu Klea and Omdurman, is sent to Mafeking, 'the place of stones', to recruit and train men for the fighting ahead. Amber, his wife, the successful novelist, accompanies him - eager to see more of the country her husband is about to risk his life for. But when war is declared, Amber must flee with their baby son and pray for her husband's survival against impossible odds. Eight hundred miles to the south, in Cape Town, Ryder Courtney - adventurer, maverick, industrialist - is using his wealth and connections to bankroll the British war effort. His artist wife Saffron, frustrated by stuffy Cairo society, has joined him with their three children. There is peace in the Courtney household, or so Saffron believes, until their eldest son, Leon, stows away on a train to the front line, determined to join his distinguished uncle, Penrod Ballantyne, in changing the course of history. Saffron and Ryder have no choice but to leave the safety of the Cape Colony and follow. Leon is convinced that his parents are without honour and courage. Little does he realise that he has no chance of escaping the people they used to be. Two families torn apart, caught up in a battle for the heart of a country at war with itself.